Adsorption and growth of Vibrio cholerae on chitin. - Nalin, D R (1979)
Incubation of Vibrio cholerae of O-group serotype 1 with chitin particles resulted in adsorption of vibrios onto chitin; chitin-adsorbed V. cholerae survived exposure to acid better than nonadsorbed vibrios. V. cholerae multiplied in dialyzed chitin suspended in 4.2% NaCl, suggesting that adherence to ingested chitin of crustacea might be of epidemiological significance by providing a substrate for vibrio multiplication as well as protection from gastric acid during stomach transit.